Stress Management Strategies Employed by Lecturers of Special Education in Selected Public Universities of Ghana (British Journal of Multidisciplinary and Advanced Studies, 2023)
The study investigated stress management strategies employed by lecturers of special education in selected public Universities in Ghana. It adopted a descriptive survey research design. A sample of 22 lecturers of special education students was selected from three (3) public universities using census technique. A four-point likert scale questionnaire was used to collect data from the respondents. The study revealed that the teachers experience stressful situations in their duties, and they used various stress coping strategies known to them. The study recommended that management of the universities should employ additional special education lecturers to reduce the workload of individual lecturers. Also, that management of the universities should sensitize lecturers to make use of counselling services provided by the universities.